2022
DOI: 10.1039/d2cc03286d
|View full text |Cite
|
Sign up to set email alerts
|

Structural adaptations of electrosprayed aromatic oligoamide foldamers on Ag(111)

Abstract: Aromatic foldamers are promising for applications such as molecular recognition and molecular machinery. For many of these, defect free, 2D-crystaline monolayers are needed. To this end, submonolayers were prepared in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…[21][22][23][24] The emergence of electrospray ionization (ESI), a so ionization technique that enables transferring of intact ions from solution into a mass spectrometer, has facilitated the deposition of a broad range of ions for the analysis of their structures and reactivities on substrates. [25][26][27][28][29][30][31][32] For example, scanning tunneling microscopy of cis-bis(isothiocyanato)bis(2,2 0bipyridyl-4,4 0 -dicarboxylato)-ruthenium(II) on a Au(III) surface revealed that its gas-phase geometry is distorted on the surface to maximize ligand-surface interactions. 33 In another study, so landed vanadium-benzene sandwich clusters were shown to orient on a CH 3 -terminated self-assembled monolayer on gold (HSAM) to maximize interactions between the aromatic rings of the cluster and methylene groups of the HSAM.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] The emergence of electrospray ionization (ESI), a so ionization technique that enables transferring of intact ions from solution into a mass spectrometer, has facilitated the deposition of a broad range of ions for the analysis of their structures and reactivities on substrates. [25][26][27][28][29][30][31][32] For example, scanning tunneling microscopy of cis-bis(isothiocyanato)bis(2,2 0bipyridyl-4,4 0 -dicarboxylato)-ruthenium(II) on a Au(III) surface revealed that its gas-phase geometry is distorted on the surface to maximize ligand-surface interactions. 33 In another study, so landed vanadium-benzene sandwich clusters were shown to orient on a CH 3 -terminated self-assembled monolayer on gold (HSAM) to maximize interactions between the aromatic rings of the cluster and methylene groups of the HSAM.…”
Section: Introductionmentioning
confidence: 99%